Do Gender and School Accreditation Affect Motivation? - Nindya, Sella Ayu; Aridah, Aridah; Iswari, Weningtyas Parama; Rusmawaty, Desy (English Department, Universitas Negeri Surabaya, 2024)
This research studied student motivation in light of Dörnyei’s L2 Motivational Self System theory. There are three motivational dimensions: Ideal-L2 Self, Ought-to L2 Self, and Language Learning Experience in this theory. According to the idea, this research studied whether individual variables (gender and school accreditations) influence students’ motivation in private senior high schools. This study used a quantitative survey research methodology. This survey included second-grade pupils from seventeen private high schools in Samarinda. 193 students were chosen as the sample using random cluster selection and random individual sampling. This research used the English Learner Questionnaire (ELQ) developed by Dörnyei and Taguchi. This study used SPSS 25 of descriptive and inferential statistics to analyze the data. The data revealed that private high school students in Samarinda were highly motivated (M = 4.27) to study the English language. In addition, a statistical analysis revealed female pupils demonstrated greater motivation than male classmates. In addition, the findings for the relationship between school accreditations and student motivation revealed that school accreditations do not predict learners’ motivation. Based on the L2 Motivational Self System, pupils at private senior high schools in Samarinda were highly motivated. Their motivation was often defined by gender, but not by educational attainment.